Ethnic minority health in Vietnam: a review exposing horizontal inequity - Mats Målqvist; Dinh Thi Phuong Hoa; Nguyen Thanh Liem; Anna Thorson; Sarah Thomsen (Global Health Action, 2013)
Background: Equity in health is a pressing concern and reaching disadvantaged populations is necessary to close the inequity gap. To date, the discourse has predominately focussed on reaching the poor. At the same time and in addition to wealth, other structural determinants that influence health outcomes exist, one of which is ethnicity. Inequities based on group belongings are recognised as ‘horizontal’, as opposed to the more commonly used notion of ‘vertical’ inequity based on individual characteristics. Objective: The aim of the present review is to highlight ethnicity as a source of horizontal inequity in health and to expose mechanisms that cause and maintain this inequity in Vietnam. Design: Through a systematic search of available academic and grey literature, 49 publications were selected for review. Information was extracted on: a) quantitative measures of health inequities based on ethnicity and b) qualitative descriptions explaining potential reasons for ethnicity-based health inequities. Results: Five main areas were identified: health-care-seeking and utilization, maternal and child health, nutrition, infectious diseases, and oral health and hygiene. Evidence suggests the presence of severe health inequity in health along ethnic lines in all these areas. Research evidence also offers explanations derived from both external and internal group dynamics to this inequity. It is reported that government policies and programs appear to be lacking in culturally adaptation and sensitivity, and examples of bad attitudes and discrimination from health staff toward minority persons were identified. In addition, traditions and patriarchal structures within ethnic minority groups were seen to contribute to the maintenance of harmful health behaviors within these groups. Conclusion: Better understandings of the scope and pathways of horizontal inequities are required to address ethnic inequities in health. Awareness of ethnicity as a determinant of health, not only as a covariate of poverty or living area, needs to be improved, and research needs to be designed with this in mind.